Risk Attitudes and Wage Growth: Replication and Reconstruction - Santi Budria; Luis Diaz-Serrano; Ada Ferrer-i-Carbonell; Joop Hartog (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We replicate Shaw (1996) who found that individual wage growth is higher for individuals with greater preference for risk taking. Expanding her dataset with more American observations and data for Germany, Spain and Italy, we find mixed support for the earlier results. We present and estimate a new model and find that in particular the wage level is sensitive to attitudes towards risk taking.
Keywords: J24; J30; 330; wage growth; risk; post-school investment